Sri Lanka - Selected Public Expenditure Issues, 2003/2004 - World Bank (Washington, DC, 2014)
This sector report for Sri Lanka - Selected public expenditure issues, 2003/2004 concentrates on the major expenditure issues facing the Government of Sri Lanka. The topic of government revenues is also, albeit briefly, touched on. The policy notes commence with a look at three overarching issues of concern for fiscal policy. The first focus is on the sustainability of the rapidly rising public debt and persistent fiscal deficits. Next, a potential contingent liability, the public service pension scheme, is examined. The note looks at the budgetary impact of the pension scheme and its medium- to long-term financial viability. The final cross-cutting expenditure issue investigated-public sector pay and employment-is a critical subject for Sri Lanka, a country with one of the highest per capita staffing rates in the developing world. The analysis reviews the ability of the administration to deliver services effectively to its citizens, particularly in a setting marked by the proliferation of various institutions with unclear mandates and overlapping functions.